Rawls and Piketty: the philosophical aspects of economic inequality - Goran Sunajko (Editura ASE Bucuresti, 2016)
This paper discusses a key contemporary problem, that of inequality. Certainly, the most visible inequality today is economic inequality, which is not only a characteristic found today, but is also the result of a long historical development. The problem arises when inequality becomes artificial (produces itself) and thus becomes a matter of social sciences and humanities. At this point, the question of economic inequality becomes a non-economic issue and thus opens the possibility of formulating such principles that will be able to reduce the issue to a minimum. This paper discusses this possibility, while referring to Thomas Piketty’s book on capital in relation to John Rawls’s principles of justice to which Piketty refers to.